Aplicação da versão em português do instrumento abreviado de avaliação da qualidade de vida "WHOQOL-bref" Application of the Portuguese version of the abbreviated instrument of quality life WHOQOL-bref - Marcelo PA Fleck; Sérgio Louzada; Marta Xavier; Eduardo Chachamovich; Guilherme Vieira; Lyssandra Santos; Vanessa Pinzon (Universidade de São Paulo, 2000)
INTRODUÇÃO: A necessidade de instrumentos de rápida aplicação determinou que o Grupo de Qualidade de Vida da Organização Mundial de Saúde desenvolvesse a versão abreviada do WHOQOL-100, o WHOQOL-bref. Este instrumento consta de 26 questões divididas em quatro domínios: físico, psicológico, relações sociais e meio ambiente. O objetivo deste estudo é a apresentação do teste de campo brasileiro do WHOQOL-bref. MÉTODOS: O WHOQOL-bref, o BDI e o BHS foram aplicados numa amostra de 300 indivíduos na cidade de Porto Alegre. RESULTADOS/CONCLUSÕES: O Instrumento mostrou características satisfatórias de consistência interna, validade discriminante, validade de critério, validade concorrente e fidedignidade teste-reteste. O WHOQOL-bref alia um bom desempenho psicométrico com praticidade de uso o que lhe coloca como uma alternativa útil para ser usado em estudos que se propõe a avaliar qualidade de vida no Brasil. INTRODUCTION: The need of short instruments to evaluate Quality of life determines World Health Organization Quality of Life Group (WHOQOL Group) to develop an abbreviated version of the WHOQOL-100, the WHOQOL-bref. The objective is to present the Brazilian field trial of the WHOQOL-bref. METHODS: WHOQOL-bref is composed by 26 questions divided in four domains: physical, psychological, social relationships and environment. The evaliation instrument, BDI (beck depression inventory) and BHS (beck hopelessness scale) were used in a 300 subjects sample in Porto Alegre, South Brazil. RESULTS/CONCLUSIONS: The instrument showed a good performance concerning internal consistency, discriminant validity, criterion validity, concurrent validity and test-retest reliability. The intrument allies good psychometric performance and practicity for use which puts it as an interesting option to evaluate quality of life in Brazil.